Prognostic Value of Ferroptosis-Related Biomarkers ACSL4 and GPX4 in Critically Ill Patients: A Systematic Review and Meta-Analysis: ACSL4 and GPX4 in Critical Illness Prognosis - Gao, Yue; Wang, Chengxiang (Journal of Medical Biochemistry, 2026)
Background: Ferroptosis is a regulated form of cell death characterized by iron-dependent lipid peroxidation and has been increasingly implicated in the pathogenesis of severe infections and critical illness. Acyl-CoA synthetase long-chain family member 4 (ACSL4) and glutathione peroxidase 4 (GPX4) are key regulators of ferroptosis and may serve as clinically useful biomarkers for prognostic assessment. This systematic review and meta-analysis aimed to evaluate the prognostic significance of serum ACSL4 and GPX4 levels in critically ill patients with severe infections.Methods: A systematic search of PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang Data, and China Biology Medicine Disc (CBM) was conducted from database inception to March 2026. Observational studies evaluating the association between serum ACSL4 and/or GPX4 levels and clinical outcomes in critically ill patients were included. Study quality was assessed using the Newcastle–Ottawa Scale (NOS). Meta-analysis was performed using RevMan 5.4 and Stata 16.0. Odds ratios (ORs) and 95% confidence intervals (CIs) were pooled using random-effects models. Diagnostic performance was evaluated using receiver operating characteristic (ROC) data where available. Heterogeneity, sensitivity analyses, and publication bias assessments were conducted according to standard methodological approaches.Results: A total of 42 records were identified, and two high-quality prospective cohort studies involving 437 critically ill patients were included. NOS scores ranged from 8 to 9 points. Meta-analysis demonstrated that ferroptosis-related biomarkers were significantly associated with short-term mortality. Reduced serum GPX4 (OR=1.076, 95% CI: 1.036–1.119), reduced GSH/GSSG ratio (OR=1.258, 95% CI: 1.161–1.364), and elevated serum ACSL4 (OR=4.00, 95% CI: 2.00–8.00) were independently associated with adverse outcomes. The pooled OR was 1.76 (95% CI: 1.03–3.01), indicating a significantly increased risk of short-term mortality in patients exhibiting ferroptosis pathway dysregulation. Regarding prognostic performance, ACSL4 alone yielded an area under the curve (AUC) of 0.713, whereas GPX4 alone showed limited predictive ability (AUC=0.573). Combined assessment of GPX4 and GSH/GSSG improved predictive performance substantially (AUC=0.841). Sensitivity analyses confirmed the robustness of the findings.Conclusion: Abnormal expression of ferroptosis-related biomarkers, particularly elevated ACSL4 and reduced GPX4 levels, is associated with poor short-term outcomes in critically ill patients with severe infections. Combined evaluation of ferroptosis-related markers may improve risk stratification and prognostic assessment. These findings support the potential clinical utility of the ACSL4/GPX4 axis as a biomarker system and highlight ferroptosis as a promising therapeutic target in critical illness.
Keywords: ACSL4; GPX4; Ferroptosis; Critical illness; Sepsis; Community-acquired pneumonia; Prognosis